Benefit finding among parents of young children with type 1 diabetes. Issue 5 (20th May 2019) - Pierce, Jessica S.; Wasserman, Rachel; Enlow, Paul; Aroian, Karen; Lee, Joyce; Wysocki, Tim
Abstract: Benefit finding, perceived positive effects of adversity, has been associated with psychological well‐being in people with chronic illnesses and with better adherence for adolescents with type 1 diabetes (T1D). Our qualitative research with parents of young children (< 6 years old) with T1D indicated that benefit finding (BF) is a common parental coping mechanism, but no tools exist to measure BF in parents. We determined psychometric properties of the Diabetes Benefit Finding Scale for Parents (DBFS‐P), a 16‐item questionnaire adapted from the validated adolescent version. Parents of young children with T1D (n = 172) were participants in a randomized trial of an online intervention. We examined the DBFS‐P factor structure through principal component analysis (PCA); internal consistency through Cronbach's alpha; convergent validity via bivariate correlations between the DBFS‐P and measures of parental depression, anxiety, T1D self‐efficacy, and hypoglycemia fear; and discriminant validity via bivariate correlations between the DBFS‐P and measures of parental somatization and child behavior problems. PCA revealed one factor (56.47% variance) with Cronbach's α = 0.95. Convergent validity of the DBFS‐P was supported by significant correlations with parental depression (r = −0.35, P  < 0.001), anxiety (r = −0.20, P  = 0.008), T1D self‐efficacy (r = 0.36, P  < 0.001), and hypoglycemia fear (r = 0.27, P  < 0.001). Non‐significant correlations with parental somatization (r = −0.06, P  = 0.42) and child behavior problems (r = −0.12, P  = 0.14) support its discriminant validity. The DBFS‐P demonstrated good psychometric properties as a tool for assessing BF among caregivers.